2021
DOI: 10.1080/14756366.2021.1953996
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethyl-substituted 3,5-bis(arylidene)-4-piperidones as potential anti-hepatoma and anti-inflammation agents by inhibiting NF-кB activation

Abstract: Trifluoromethyl-substituted 3,5bis(arylidene)-4-piperidones as potential anti-hepatoma and anti-inflammation agents by inhibiting NF-кB activation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Docking studies were performed at the hA 2A and hA 2B AR binding sites to simulate the interaction of compound 7i with these two receptors. The binding modes of compound 7i at the hA 2A AR cavity were analysed by docking simulations using the C-DOCKER protocol of Discovery Studio 2017 R2 39 . The crystal structure of hA 2A AR in complex with antagonist ZM241385 (PDB ID: 5IU4) was retrieved from the Protein Data Bank ( http://www.rcsb.org/pdb ) for the docking calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Docking studies were performed at the hA 2A and hA 2B AR binding sites to simulate the interaction of compound 7i with these two receptors. The binding modes of compound 7i at the hA 2A AR cavity were analysed by docking simulations using the C-DOCKER protocol of Discovery Studio 2017 R2 39 . The crystal structure of hA 2A AR in complex with antagonist ZM241385 (PDB ID: 5IU4) was retrieved from the Protein Data Bank ( http://www.rcsb.org/pdb ) for the docking calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between these two compounds is the presence of ethyl in compound (a) and trifluoromethyl in compound (b). A study found that trifluoromethyl may affect the electrical properties of the target chemicals, and its lipophilicity can promote membrane permeability (Cong et al, 2021). However, comparing compound (b) to non-selective COX inhibitor indomethacin, the GI side effects for compound (b) are less severe but not as efficient as a COX-2 inhibitor, celecoxib.…”
Section: Scheme 5 Synthesis Of Ibuprofen-amide Derivativesmentioning
confidence: 99%